Origin of Enriched Regulatory T Cells in Patients Receiving Combined Kidney–Bone Marrow Transplantation to Induce Transplantation Tolerance. Issue 8 (10th April 2017) - Sprangers, B.; DeWolf, S.; Savage, T. M.; Morokata, T.; Obradovic, A.; LoCascio, S. A.; Shonts, B.; Zuber, J.; Lau, S. P.; Shah, R.; Morris, H.; Steshenko, V.; et al.
Abstract : We examined tolerance mechanisms in patients receiving HLA‐mismatched combined kidney–bone marrow transplantation (CKBMT) that led to transient chimerism under a previously published nonmyeloablative conditioning regimen (Immune Tolerance Network study 036). Polychromatic flow cytometry and high‐throughput sequencing of T cell receptor‐β hypervariable regions of DNA from peripheral blood regulatory T cells (Tregs) and CD4 non‐Tregs revealed marked early enrichment of Tregs (CD3 + CD4 + CD25 high CD127 low Foxp3 + ) in blood that resulted from peripheral proliferation (Ki67 + ), possibly new thymic emigration (CD31 + ), and, in one tolerant subject, conversion from non‐Tregs. Among recovering conventional T cells, central memory CD4 + and CD8 + cells predominated. A large proportion of the T cell clones detected in posttransplantation biopsy specimens by T cell receptor sequencing were detected in the peripheral blood and were not donor‐reactive. Our results suggest that enrichment of Tregs by new thymic emigration and lymphopenia‐driven peripheral proliferation in the early posttransplantation period may contribute to tolerance after CKBMT. Further, most conventional T cell clones detected in immunologically quiescent posttransplantation biopsy specimens appear to be circulating cells in the microvasculature rather than infiltrating T cells. Abstract : In patients receiving HLA‐mismatched combined kidney–bone marrow transplantation to induce transplantation tolerance, polychromatic flow cytometry and high‐throughput T cell receptor sequencing reveal an early enrichment of regulatory T cells, probably arising from new thymic emigration and lymphopenia‐driven peripheral proliferation, though the T cell receptors detected are likely from circulating T cells in the allograft microvasculature rather than infiltrating T cells.